Life's too short top tips and insider cheats for the modern woman - Saunders, Grace (Headline, 2012)
"Grace Saunders shares her shortcuts to success at work, at home and at play, along with terrific tips from those in the know. Whether you're a single lady, a committed career woman or a mega-busy mum, this book should be your bible."